Comprehensive sexuality education and adjacent prevention strategies for adolescent sexual violence: a scoping review of consent, empowerment and bystander action - Fanni Hanifa; Nita Arisanti; Tetti Solehati; Rusnani Ab Latif; Meita Dhamayanti (Frontiers in Public Health, 2026)
Introduction Adolescent sexual violence is a persistent public-health, educational, and human-rights problem. Comprehensive Sexuality Education (CSE) is frequently proposed as a primary prevention approach, but evidence relevant to sexual violence is distributed across CSE, consent and respectful-relationships education, gender-transformative programming, empowerment, bystander intervention, and whole-school safeguarding. This scoping review mapped how CSE and explicitly related prevention strategies address adolescent sexual violence, which mechanisms and outcomes they emphasize and where evidence gaps remain. Methods Following JBI guidance and PRISMA-ScR, 18 sources were charted and synthesized through a deductive–inductive thematic process. Results The mapped sources comprised intervention evaluations, systematic and narrative reviews, qualitative and systems studies, program or adaptation papers, a protocol, and commentary. Four interconnected domains were identified: consent and relational ethics; empowerment, gender norms, and youth agency; bystander and peer mechanisms; and implementation and school-system conditions. The literature suggests that multicomponent approaches can improve knowledge, attitudes, communication, self-efficacy, and readiness to intervene; evidence for sustained reductions in perpetration or victimization is less consistent. Null or limited effects were reported for some behavioral outcomes, and communication diffusion did not necessarily produce behavioral diffusion. Most evidence came from high-income countries, with limited context-specific evidence from low- and middle-income countries. Discussion CSE should therefore be understood as a defined curriculum-based, rights-oriented approach that may incorporate adjacent violence-prevention strategies without being equated with them. Future studies should use longitudinal behavioral outcomes, implementation and fidelity measures, intersectional analyses, and culturally grounded whole-school designs.